Projeto para produção de impermeabilização: estudo de caso - Tortelli, Maria Eduarda (2023)
As important as the product projects are the production projects. In them, action plans are defined, such as sequences, materials and methods to be used according to the progress of the work. A considerable stage of civil construction is waterproofing, which aims to protect constructions against the deleterious action of fluids, vapors and humidity, often being left out when related to other projects, or carried out empirically, without the plan of specific action and in disagreement with the criteria required by the standards, making future repairs difficult and causing additional costs. This study presents the reasons why a Waterproofing Project is important, together with a study of the applicability of this project model.